2013
DOI: 10.1080/10824669.2013.833047
|View full text |Cite
|
Sign up to set email alerts
|

Predicting High School Graduation and College Enrollment: Comparing Early Warning Indicator Data and Teacher Intuition

Abstract: Each year, more districts implement early warning systems (EWS). These EWS predict negative student outcomes, such as dropping out, before they occur. Predictions are then used to match at-risk students to appropriate supports and interventions. Research suggests that these systems are useful in ensuring educators respond to student needs early, generating conversation around specific students at risk of dropping out. However, no research considers what new information teachers gain from having a specific pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Teachers' perceptions furthermore indicate great differences in how decisions are made within and between schools. These findings support prior research on how teachers' perceptions of student characteristics influence decisions about placement of students in specific groups (e.g., Soland, 2013;Van Houtte & Demanet, 2016), add to what is known about influencing factors and limitations in group decision-making by teachers, and offer a more detailed picture of how allocation decisions are made in practice (Bol et al, 2014;Elffers, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…Teachers' perceptions furthermore indicate great differences in how decisions are made within and between schools. These findings support prior research on how teachers' perceptions of student characteristics influence decisions about placement of students in specific groups (e.g., Soland, 2013;Van Houtte & Demanet, 2016), add to what is known about influencing factors and limitations in group decision-making by teachers, and offer a more detailed picture of how allocation decisions are made in practice (Bol et al, 2014;Elffers, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…They find no student–teacher interaction effect on academic expectations of students. Similarly, using baseline data on eighth-grade students from NELS:88 and a student fixed-effect approach, Soland (2013) does not find evidence that race or sex congruence between students and teachers matters for teachers’ postsecondary expectations for students. Although observational, several studies find that Black teachers are more likely than White teachers to (a) think Black students will enroll in or complete college, (b) be optimistic about Black students’ future academic careers, and (c) see future educational potential in Black students (Beady & Hansell, 1981; DeMeis & Turner, 1978; Ehrenberg et al, 1995).…”
Section: Background Literature and Theoretical Contextmentioning
confidence: 83%
“…Studies show that teachers are quite good at predicting which students will drop out. In my work (Soland, 2013), 10th-grade teachers accurately predicted which students would drop out 89% of the time compared to 88% for EWI using statistical models. As one might suspect, teachers factored information on student attitudes and behavior into these predictions, which helped account for their accuracy.…”
Section: Predictive Analytics In Education Is Uniquementioning
confidence: 88%
“…First, teachers may base their predictions on less than objective information. For example, I found that teachers were likelier to predict that Latino and African-American students would drop out (Soland, 2013). Even more troubling, these same teachers were likelier to mistakenly predict that minority students would fail to graduate.…”
Section: Predictive Analytics In Education Is Uniquementioning
confidence: 99%